A Critical Precaution — Immunizations in Reproductive Health - Buckley, Rita (MD Conference Express, 2011)
Vaccination is one of the most efficient and cost-effective ways to prevent maternal and neonatal morbidity and mortality. For women in their reproductive years, it serves two roles—primary prevention of disease and protection for infants. This article discusses vaccines and their recommended use in reproductive-age women.